Compute
∑ n = 0 ∞ n 4 + n 2 + 1 n
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution
I started by looking at the first few partial sums: 3 1 , 7 3 , 1 3 6 , 2 1 1 0 , . . .
It's pretty clear that the partial sums are approaching 2 1 but we need to prove this.
For each partial sum S k , if we look at the values of 2 1 − S k , we get 6 1 , 1 4 1 , 2 6 1 , 4 2 1 , . . .
The numerators seem to always be 1 , and the denominators are 6 , 1 4 , 2 6 , 4 2 , . . . . The second differences in these numbers are constant (namely 4), which means they fit a quadratic equation (with leading coefficient 2). Suppose the denominators are of the form 2 x 2 + a x + b . Plugging in x = 1 gives 2 + a + b = 6 , and plugging in x = 2 gives 8 + 2 a + b = 1 4 . Therefore a = 2 and b = 2 .
Therefore, the pattern appears to be 2 1 − S k = 2 k 2 + 2 k + 2 1 , or S k = 2 ( k 2 + k + 1 ) k 2 + k .
We see that this formula holds true for the first few cases, so naturally we use induction to prove it is always true.
Suppose S k = 2 ( k 2 + k + 1 ) k 2 + k for some k ∈ N . Then, S k + 1 = S k + ( k + 1 ) 4 + ( k + 1 ) 2 + 1 k + 1 = 2 ( k 2 + k + 1 ) k 2 + k + ( ( k + 1 ) 2 + 1 ) 2 − ( k + 1 ) 2 k + 1 = 2 ( k 2 + k + 1 ) k 2 + k + ( ( k + 1 ) 2 + ( k + 1 ) + 1 ) ( ( k + 1 ) 2 − ( k + 1 ) + 1 ) k + 1 = 2 ( k 2 + k + 1 ) k 2 + k + ( k 2 + 3 k + 3 ) ( k 2 + k + 1 ) k + 1 = 2 ( k 2 + 3 k + 3 ) ( k 2 + k + 1 ) ( k 2 + k ) ( k 2 + 3 k + 3 ) + 2 ( k + 1 ) = 2 ( k 2 + 3 k + 3 ) ( k 2 + k + 1 ) ( k + 1 ) ( k 3 + 3 k 2 + 3 k + 2 ) = 2 ( k 2 + 3 k + 3 ) ( k 2 + k + 1 ) ( k + 1 ) ( k + 2 ) ( k 2 + k + 1 ) = 2 ( ( k + 1 ) 2 + ( k + 1 ) + 1 ) ( k + 1 ) 2 + ( k + 1 )
Therefore, by induction, we have that S k = 2 ( k 2 + k + 1 ) k 2 + k for all k ∈ N . Therefore,
lim k → ∞ S k = lim k → ∞ 2 ( k 2 + k + 1 ) k 2 + k = lim k → ∞ ( 2 1 − 2 k 2 + 2 k + 2 1 ) = 2 1
Hence the answer is 2 1 .
Problem Loading...
Note Loading...
Set Loading...
Note that n 4 + n 2 + 1 n = n 4 + 2 n 2 + 1 − n 2 n = ( n 2 + 1 ) 2 − n 2 n = ( n 2 − n + 1 ) ( n 2 + n + 1 ) n = 2 n 2 − n + 1 1 − n 2 + n + 1 1
Now note that ( n + 1 ) 2 − ( n + 1 ) + 1 1 = n 2 + n + 1 1
Thus, the series n = 0 ∑ ∞ 2 n 2 − n + 1 1 − n 2 + n + 1 1 is a telescoping one.
Thus, n = 0 ∑ ∞ 2 n 2 − n + 1 1 − n 2 + n + 1 1 = 2 1 2 − 1 + 1 1 = 2 1 and we are done.